Women’s Ambition, Ambitious Women: The Case of Caesar’s Household During The Julio-Claudian Era (Journal of Management and Social Sciences, 2017)
AbstractMost scholarship on women and their position in antiquity generally agrees that women’s status was largely low. Relatedly, in the ancient Republican Rome, women had no significant political, economic, legal and social rights. However, by the Imperial period, it appeared that the status quo was altered as many Roman women pursued tall ambitions such as desire for wealth, political power, fame, elegance, adornment and control of their families. Using the mistresses, wives, mothers, and daughters that were either married or related to first century Julio-Claudian Caesars as a case study, this paper examined women’s struggle for ambition, dominance, and control of the Roman Empire. Approached chronologically through a method of content analysis of archival materials and the evidence provided by Roman writers such as Tacitus, Livy, Sallust, and Seneca, the paper highlighted some ambitious behaviours of selected women within the period 31B.C. – A.D.68. Rather than exude the virtues of true matronae (noble women) to advance their society, Caesars’ women exhibited flagrant indiscipline, immorality, and wickedness in form of subtle naggings, conspiracies, promiscuity, prostitution, debaucheries, poisonings, and murders of relations in order to achieve their varied notorious ambitions. The paper concluded specifically that these women’s drives ultimately contributed to the collapse of sociopolitical order under the Julio-Claudian dynasty.Keywords  Women, ambition, Julio-Claudian dynasty, imperial Rome